Economic Viability of Community Gardens in Semarang City - Rahoyo Rahoyo; Teti Susilowati; Sri Purwantini (Universitas Negeri Semarang, 2025)
Numerous studies have shown that urban agriculture makes substantial contributions to poverty reduction, reduces unemployment, and improves food security. Unfortunately, research on the profitability and economic viability of urban agriculture remains limited. This research aims to explore the economic viability of community gardens as a form of urban agriculture in Semarang City, Indonesia. Semarang city was chosen due to its active implementation of urban farming programs initiated by the municipal government. The research employed a qualitative approach involving 24 participants spread across all sub-districts in Semarang. Data were collected through questionnaires, in-depth interviews, observations, and documentation. Thematic was applied to explore the research findings with the help of NVivo 12 Pro software. The findings indicate that most community gardens operate at a financial loss, showing weak economic viability. Even so, they continue to function sustainably, driven not by profit but by government programs, social cohesion, and environmental concern. This reveals a paradox: community gardens may not generate a profit, yet they remain socially sustainable – sustained more by policy than by market forces. These findings suggest that their sustainability relies more on institutional and communal support than on profit generation. Strengthening government facilitation and community empowerment is essential to ensure their long-term continuity.